Analisis Trafik Telekomunikasi Menggunakan Model Sistem Sharing - Astuti, Yenni; Rudianto, Daniel Teguh; Prasetya, Agga (Sekolah Tinggi Teknologi Adisutjipto, 2016)
The fast progress in telecommunication, especially in data communication, makes anyone get the information they need easily. It also makes more traffic in the channel. The intensity of the traffic is one of the parameters that considered by the IT unit. In this paper, the intensity of the traffic in institution A is calculated using Sharing System Teletraffic Model. As the result, the arrival rate and service rate are 1,129,139 bits per second and 16.566.740 bits per second. Keywords—telecommunication traffic, sharing system, internet